Monetary and macroprudential policy games in a monetary union - Richard Dennis; Pelin Ilbas (National Bank of Belgium, 2016)
We use the two-country model of the euro area developed by Quint and Rabanal (2014) to study policymaking in the European Monetary Union (EMU). In particular, we focus on strategic interactions: 1) between monetary policy and a common macroprudential authority, and; 2) between an EMU-level monetary authority and regional macroprudential authorities. In the first case, price stability and financial stability are pursued at the EMU level, while in the second case each macroprudential authority adopts region-specific objectives. We compare cooperative equilibria in the simultaneous-move and leadership solutions, each obtained assuming policy discretion. Further, we assess the effects on policy performance of assigning shared objectives across policymakers and of altering the level of importance attached to various policy objectives.
Keywords: E42; E44; E52; E58; E61; 330; Monetary policy; macroprudential policy; policy coordination; Geldpolitik; Finanzmarktaufsicht; Spieltheorie; Zwei-Länder-Modell; Eurozone